(untitled) (مجلة البحوث الأكاديمية, 2018)
Hepatitis B virus is considered as a serious public health problem. Infection of this virus might lead to more serious clinical consequences. This study was conducted to estimate and compare the prevalence and trend of HBV infection among blood donors of three cities in Libya, Tripoli, Misurata and Zleetin and to explore the effect of Libyan incidences on the trend of the infection. A retrospective study was carried out on 72146 nationwide voluntary blood donors in four blood banks, covering the three cities over a period of four years (2009-2013), where serologic screening assay for HBsAg was performed. Findings showed statistically significant differences (P<0.05) in the prevalence of the virus among the cities over the period mentioned. Results also indicated an increasing trend in the overall prevalence of the virus in Tripoli and decreasing trend in Misurata and Zleetin (P >0.05) after Libyan incidences with no statistically significant difference. Sensitive tests such as nucleic acid amplification are recommended for more accurate results